Kemampuan Berpikir Kreatif Mahasiswa Pendidikan Biologi dalam Penyelesaian Masalah Ekologi Tumbuhan - Yuliani, Anisa; Dharmono, Dharmono; Zaini, Muhammad (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
The 2013 curriculum has a pattern in which to create a creative Indonesian human being. The creative thinking abilities is important because it makes learners have many ways to solve problems with different perceptions and concepts. Components of creative thinking abilities include fluency, flexibility, and novelty. Problem solving can be used to increase motivation and cultivate creative traits. The purpose of this research is to describe the achievement aspect of each level of student’s creative thinking ability Program Biology Education of Lambung Mangkurat University in problem solving of plant ecology. This research method using quantitative approach and descriptive research type. Quantitative data from the result of student answers do written tasks that will be analyzed in percentage, then converted into data description. The result of achievement aspect of each level of student’s creative thinking ability student of Biology Education Lambung Mangkurat University in problem solving namely the creative level with fluency aspect is high, flexibility and novelty is medium. The quite creative level with fluency, flexibility and novelty is medium. The less creative level with fluency is medium, flexibility and novelty is low.